TEACHERS' VIEWS OF ACADEMIC ACHIEVEMENT AND COMMUNITY INVOLVEMENT OF STUDENTS WITH HIGH-FUNCTIONING AUTISM - Natasha Stanojkovska-Trajkovska; Brankica Angelevska
High-functioning autism is a pervasive developmental disorder whose prevalence is increasing nowadays. That opens the question about the success in the academic achievements of the students with high-functioning autism and the influence it has in their inclusion in all the aspects of everyday life. Research carried out in this field, shows that the students with high-functioning autism in all-inclusive schools achieve better academic success and therefore it is easier for them to adapt in the environment. The purpose of this research is to determine whether the inclusion, the awareness of the educators in the course of teaching the students with high-functioning autism and the collaboration with the special educators and parents, would benefit the improvement of the academic success. The research was carried out in all the elementary, secondary, public and private schools in the city of Skopje, including 115 participants throughout the period of one year.The results show that high-functioning autism students do not achieve the expected academic results throughout all the parts of education and they are not completely integrated in the community. According to the results of our research, we can conclude that even though our country provides complete inclusion of the students withhigh-functioning autism, the necessary conditions are not yet met to enable improvement in academic achievement and integration in society.The research was conducted with support of Questionnaire for assessing the awareness and attitudes of teachers about the academic achievement and inclusion in the community of persons with high-functioning autismand Asperger Test for Children. The interview technique was also carried out with some of the teachers from the mentioned schools